Assessement variability of annual daily maximum rainfall of Pahang, Malaysia - Izyan Shahirah Aimi, Shaharuddin (2015)
This paper deals with a study on rainfall characteristics of Pahang, for the period 1998 to 2013. In December 2014 flooding caused by torrential rainfall had drowned the main roads in the state of Pahang. As a result, the operating aid to flood victims face difficulties. The main objective of this study was to asses the variability of annual daily maximum rainfall. Daily rainfall data from satellite images Tropical Rainfall Measuring Mission (TRMM) downloaded from a database of public domain. Then daily rainfall data for each major city in the state of Pahang retrieved using Geographic Information System (GIS). Gumbel distribution function were applied to estimate expected return period of extreme rainfall event. Most cities in the State receiving the highest number of monthly maximum annual rainfall during northeast monsoon (November to January). Daily rainfall is equal to or greater than 347 mm have a return period of 13 years each for Rompin, Pekan and Kuantan. However, every year the town in Pahang will receive daily maximum rainfall 37.85 mm to 128.49 mm. The results of this study can be used in a better understanding of the patterns of rainfall in the state of Pahang and can also be used as a guideline in planning the construction of infrastructure in the future